Arctic Sea Level and Surface Circulation Response to the Arctic Oscillation. Issue 13 (5th July 2018) - Armitage, Thomas W. K.; Bacon, Sheldon; Kwok, Ron
Abstract: The Arctic Oscillation (AO) is the leading mode of extratropical northern hemisphere atmospheric variability, affecting surface pressure, winds, temperature, and precipitation. Here we use an altimeter sea level record spanning 2003–2014, covering the ice‐covered and ice‐free ocean, to examine the influence of the AO on Arctic sea level and surface geostrophic circulation. AO‐driven alongshore wind anomalies drive cross‐shelf Ekman transport and opposing barotropic sea level anomalies between the shelf seas and deep basins of the Arctic Ocean, with maximum sea level anomaly differences across the shelf‐break of 3 cm per unit AO index. This pattern of sea level variability generates topographically steered (generally along‐shelf) current anomalies of around 0.5 cm/s per unit AO index. AO‐driven wind variability modulates surface currents associated with Atlantic and Pacific water inflow, with opposing inflow anomalies between the Barents Sea Opening and Bering Strait. Plain Language Summary: The Arctic Oscillation dominates large‐scale changes in atmospheric pressure, wind, temperature, and precipitation north of 20°N. This study uses satellite measurements to investigate the impact the Arctic Oscillation has on sea level and upper ocean currents in the Arctic Ocean. Winds associated with the Arctic Oscillation cause sea levels to rise in the shallow coastal shelf seas, and drop in the deeper ocean, or vice versa, depending if the Arctic Oscillation is in a positive or negative phase. These sea level patterns drive currents which generally follow the edge of the continental shelf. The Arctic Oscillation also influences the strength of the currents associated with the inflow of Atlantic Water through the Barents Sea and the inflow Pacific Water through the Bering Strait. Key Points: Monthly record of ice‐covered and ice‐free Arctic sea level and surface currents used to examine the Arctic Ocean response to the AO AO drives cross‐shelf Ekman transport, leading to opposing barotropic sea level anomalies between the Arctic shelf seas and deeper basins AO sea level variability induces along‐shelf current anomalies and modulates currents associated with Atlantic and Pacific Water inflows